Effectiveness of an active whey protein film against lipid oxidation - Andrade, M. (2017)
The aim of this work was to evaluate the effectiveness of an active whey protein film against lipid oxidation. In this frame, TBARS assay was applied to a model food packaged with an active whey protein film and with a control film, for different storage periods.